2015
DOI: 10.1073/pnas.1514012112
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 and -6 fatty acids allocate somatic and germline lipids to ensure fitness during nutrient and oxidative stress in Caenorhabditis elegans

Abstract: Animals in nature are continually challenged by periods of feast and famine as resources inevitably fluctuate, and must allocate somatic reserves for reproduction to abate evolutionary pressures. We identify an age-dependent lipid homeostasis pathway in Caenorhabditis elegans that regulates the mobilization of lipids from the soma to the germline, which supports fecundity but at the cost of survival in nutrient-poor and oxidative stress environments. This trade-off is responsive to the levels of dietary carboh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
116
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(128 citation statements)
references
References 47 publications
12
116
0
Order By: Relevance
“…C. elegans has been successfully reported as an animal model in research related to the characterization of metabolic pathways and storage and release of lipids [41][42][43]. It maintains in its cuticle and in its intestine a range of biosynthetic and catalytic enzymes, as well as reserves of lipids within its hypodermis and intestinal cells [1,42].…”
Section: Mammals E Caenorhabiditis Elegansmentioning
confidence: 99%
See 1 more Smart Citation
“…C. elegans has been successfully reported as an animal model in research related to the characterization of metabolic pathways and storage and release of lipids [41][42][43]. It maintains in its cuticle and in its intestine a range of biosynthetic and catalytic enzymes, as well as reserves of lipids within its hypodermis and intestinal cells [1,42].…”
Section: Mammals E Caenorhabiditis Elegansmentioning
confidence: 99%
“…C. elegans has been successfully reported as an animal model in research related to the characterization of metabolic pathways and storage and release of lipids [41][42][43]. It maintains in its cuticle and in its intestine a range of biosynthetic and catalytic enzymes, as well as reserves of lipids within its hypodermis and intestinal cells [1,42]. Using this small animal model, more than 300 genes were proven to cause a reduction in body fat when inactivated, as well as another 100 genes that when inactivated increased or stored fat [33,44].…”
Section: Mammals E Caenorhabiditis Elegansmentioning
confidence: 99%
“…Less common is a description of where lipids localize and measured differences in lipid abundance across tissues. However, recent work has revealed that lipid distribution can be as important as lipid accumulation 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, the major oxidative stress transcription factor is the nuclear factor erythroid 2-related factor, Nrf2, one of three Nrf paralogs (Hybertson et al 2011). To ensure efficient surveillance of redox homeostasis, several mechanisms regulate Nrf2, including those that regulate its subcellular localization and protein turnover (Marinho et al 2014).The nematode Caenorhabditis elegans utilizes a functional ortholog of mammalian Nrf proteins, SKN-1, to coordinate its oxidative stress response (Walker et al 2000; found in the regulation of the unfolded protein response and the maintenance of lipid homeostasis (Glover-Cutter et al 2013;Lynn et al 2015;Steinbaugh et al 2015). Similar to Nrf2, SKN-1 regulation is also well studied, and overlapping mechanisms of regulation exist between mammals and worms.…”
mentioning
confidence: 99%
“…The nematode Caenorhabditis elegans utilizes a functional ortholog of mammalian Nrf proteins, SKN-1, to coordinate its oxidative stress response (Walker et al 2000; found in the regulation of the unfolded protein response and the maintenance of lipid homeostasis (Glover-Cutter et al 2013;Lynn et al 2015;Steinbaugh et al 2015). Similar to Nrf2, SKN-1 regulation is also well studied, and overlapping mechanisms of regulation exist between mammals and worms.…”
mentioning
confidence: 99%